Ways to implement drug rehabilitation programme: an island model in Malaysia - Roslee Ahmad, 1973- 509496; Mohamed Sharif Mustaffa, 1959- 331966; Association of Psycological and Educational Counsellors of Asia Pacific Biennial International Conference (15th : 2004 : Johor) 477721 (Skudai : Universiti Teknologi Malaysia, 2004)
01